Kelayakan Operasi Penderita Kusta Dengan Disabilitas pada Tangan di Rumah Sakit Kusta Naob Timor Tengah Utara - Diva Alisa Darmatasia; Ika Febianti Buntoro; Nicholas Edwin Handoyo; Robertus Arian Datusanantyo (Galen: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Leprosy is an infectious disease caused by Mycobacterium leprae that can lead to disability. Surgical intervention may serve as the approaches to improve disability in patients with leprosy.  This study aimed to analyze differences in the characteristics of leprosy patients who were eligible and not eligible for surgery based on the results of surgical eligibility screening among patients with hand disabilities at Naob Leprosy Hospital, North Central Timor, in 2023.  This study employed an observational analytic design with a cross-sectional approach using a surgical eligibility screening checklist.  The results showed that most respondents were male, aged 26–45 years, had an elementary school education, and had multibacillary leprosy, with predominantly grade 4–5 motor assessments and varied sensory assessment results. Bivariate analysis indicated no significant association between motor, sensory, functional, and occupational assessments and surgical eligibility (p>0.05).  In conclusion, surgical eligibility was not significantly influenced by individual clinical parameters